Advances in databases and information systems : 23rd European conference, ADBIS 2019, Bled, Slovenia, September 8-11, 2019 : proceedings /: 23rd European conference, ADBIS 2019, Bled, Slovenia, September 8-11, 2019 : proceedings. ([2019]) - Unknown
No abstract available